6.5k views
3 votes
Expression A: (2k + 8) + (5k + 10)

Expression B: 76 + 18
Are the two expressions equivalent?
A. No, because for k = 3, the value of Expression A is 29 and the value of Expression B is 39.
B. Yes, because for k= 3, the value of Expression A is 75 and the value of Expression B is 75.
C. Yes, because for k= 3, the value of Expression A is 39 and the value of Expression B is 39.
D. No, because for k= 3, the value of Expression A is 39 and the value of Expression B is 75.

User Illuminato
by
4.5k points

1 Answer

5 votes

k = 3

Expression A:


(2k + 8) + (5k + 10) = 2k + 8 + 5k + 10 = 7k + 18 = 7*3 + 18 = 21 + 18 = 39

Expression B:


76 + 18= 94

User Jesper Tejlgaard
by
5.6k points